2021
DOI: 10.5007/1518-2924.2021.e76249
|View full text |Cite
|
Sign up to set email alerts
|

Impacto acadêmico e atenção on-line de pesquisas sobre inteligência artificial na área da saúde: análise de dados bibliométricos e altmétricos

Abstract: Objetivo: A inteligência artificial, como campo interdisciplinar, tem sua literatura presente em diversas áreas do conhecimento e suas aplicações têm oferecido importantes contribuições para os campos científicos que a ela se dedicam. Este estudo tem por objetivo analisar a produção científica sobre inteligência artificial em artigos científicos de acesso aberto na área da saúde e compreender seus indicadores de impacto. Método: Trata-se de pesquisa descritiva, exploratória e quantitativa, que utiliza técnicas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…In the same way, it is valued that the articles are published in specialized magazines of the area or branch of knowledge investigated. In this sense, several investigations identified Plos One as one of the most productive journals, partially coinciding with the rest (mainly Scientific Reports; IEEE Access) 29,31,41 . This result may be determined by the difference among the databases where the bibliometric analysis of the studies was carried out.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the same way, it is valued that the articles are published in specialized magazines of the area or branch of knowledge investigated. In this sense, several investigations identified Plos One as one of the most productive journals, partially coinciding with the rest (mainly Scientific Reports; IEEE Access) 29,31,41 . This result may be determined by the difference among the databases where the bibliometric analysis of the studies was carried out.…”
Section: Discussionmentioning
confidence: 95%
“…Although Guo et al 31 and Prema et al 43 did not identify any Latin American country as a high producer in AI and health, growing scientific production is real. In this sense, Guntijo et al 41 report in their co-authorship networks between countries the existence of cooperation with Brazil as the largest producer in Latin America. For their part, Xuan Tran et al 29 identified Brazil as the sixteenth largest producing country in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…as comunidades acadêmicas necessitam de condições para identificarem e avaliarem o desempenho das suas pesquisas por meio de indicadores adequados, como os fornecidos por estudos métricos da informação (GONTIJO; ARAÚJO, 2021).…”
unclassified
“…Diante das demandas oriundas da web social, visualiza-se a construção de novas estratégias de mensuração da produção científica, cujas formulações atuam como um mecanismo complementar às tradicionais métricas de acompanhamento do impacto das publicações científicas (BORBA; CAREGNATO, 2021;ARAÚJO, 2021). Além do mais, nesse contexto, entende-se ser necessária "a aferição de indicadores capazes de medir o grau de interesse acadêmico e social que as literaturas científicas têm recebido" (GONTIJO; ARAÚJO, 2021, p. 3).…”
unclassified